2016
DOI: 10.1002/hbm.23283
|View full text |Cite
|
Sign up to set email alerts
|

Significant reductions in human visual gamma frequency by the gaba reuptake inhibitor tiagabine revealed by robust peak frequency estimation

Abstract: The frequency of visual gamma oscillations is determined by both the neuronal excitation–inhibition balance and the time constants of GABAergic processes. The gamma peak frequency has been linked to sensory processing, cognitive function, cortical structure, and may have a genetic contribution. To disentangle the intricate relationship among these factors, accurate and reliable estimates of peak frequency are required. Here, a bootstrapping approach that provides estimates of peak frequency reliability, thereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 76 publications
4
39
2
Order By: Relevance
“…In our case, this may have been due to EEG signal to noise ratio being generally lower than that of MEG (Muthukumaraswamy & Singh, ). However, this is unlikely as the reliability of the peak frequency estimation was as good as, or at least comparable to, the findings of Magazzini et al (), indicating high signal‐to‐noise ratio. It has also been proposed that the neural mechanisms behind amplitude and frequency of gamma can be differentially modulated, with frequency more linked to the time‐constant of inhibitory processes (Magazzini et al, ).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…In our case, this may have been due to EEG signal to noise ratio being generally lower than that of MEG (Muthukumaraswamy & Singh, ). However, this is unlikely as the reliability of the peak frequency estimation was as good as, or at least comparable to, the findings of Magazzini et al (), indicating high signal‐to‐noise ratio. It has also been proposed that the neural mechanisms behind amplitude and frequency of gamma can be differentially modulated, with frequency more linked to the time‐constant of inhibitory processes (Magazzini et al, ).…”
Section: Discussionsupporting
confidence: 69%
“…It has also been proposed that the neural mechanisms behind amplitude and frequency of gamma can be differentially modulated, with frequency more linked to the time‐constant of inhibitory processes (Magazzini et al, ). To support this, when the data for the tiagabine data as presented by Magazzini et al () was subjected to DCM‐SSR by Shaw et al (), it was found that individual variability in the time constant of inhibitory interneurons was found to be significantly modulated by gamma frequency but not amplitude. Furthermore, a contribution analysis was completed in Shaw et al () to determine the key parameters contributing to gamma frequency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neural disinhibition yields higher baseline activity across frequency bands and failure of event-related activity to modulate, adapt, or be suppressed over repeated events(44). Pharmacological models altering GABAergic and glutamatergic neurotransmission confirm excitatory and inhibitory signaling contribute significantly to high-frequency oscillations(45,46). Thus, higher baseline excitation and altered stimulus-related evoked response can result from increased excitation, decreased inhibition, or a combination.…”
Section: Electrophysiology and Magnetoencephalographymentioning
confidence: 99%